Copper-molybdenum copper-copper composite material with core material with holes and preparation method of copper-molybdenum copper-copper composite material
By setting holes in the core material of copper-molybdenum copper-copper composite and filling high-thermal conductivity materials, the problem of difficult to take into account both the thermal conductivity and expansion coefficient of the existing materials is solved, and the effects of efficient heat dissipation and low thermal stress are achieved.
Patent Information
- Application Number
- CN202411899995.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
While the existing copper-molybdenum copper-copper composite materials improve thermal conductivity, the thermal expansion coefficient is difficult to effectively reduce, resulting in the inability to have both high thermal conductivity and low expansion coefficient.
The copper-molybdenum copper-copper composite material with a porous core material is used to accurately control the flow direction and speed of heat to reduce thermal stress by opening holes in the core material and filling it with high thermal conductivity silicon carbide and/or diamond materials.
It achieves a low thermal expansion coefficient and high thermal conductivity, significantly improves heat dissipation ability, extends the service life of semiconductor devices, and improves the reliability and stability of the system.
Smart Images

Figure CN119725263A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat sink materials, and in particular to the technical field of copper-molybdenum-copper-copper composite heat sink materials. Background Art
[0002] With the rapid development of technologies such as mobile communications, the Internet of Things, artificial intelligence, and power batteries, semiconductor devices are moving towards miniaturization. Under this trend, the integration of electronic materials in microelectronics technology is getting higher and higher, which will lead to more and more prominent contradictions in power density and heat dissipation of electronic equipment. If the large amount of heat generated by the device during use cannot be dissipated in time, its life and stability will be affected, so the requirements for the heat dissipation capacity of heat sink materials are constantly increasing. On the other hand, existing heat sink materials often have the problem of mismatching thermal expansion coefficients with semiconductor devices, causing devices or microelectronic circuits to fail due to thermal stress and thermal fatigue. Therefore, the development of heat sink materials with high thermal conductivity and low expansion coefficients is an urgent problem to be solved in the field of electronic packaging.
[0003] Copper-molybdenum-copper-copper three-layer or multi-layer material is one of the commonly used heat dissipation composite materials. The copper layer on its surface has good thermal conductivity and heat dissipation effects. The core molybdenum-copper layer can control the overall thermal expansion coefficient of the material within a low range while ensuring thermal conductivity and heat dissipation. By adjusting the ratio of molybdenum and copper in the core material or the layer thickness ratio of the molybdenum-copper layer and the surface copper layer, the thermal conductivity and thermal expansion coefficient of the material can also be adjusted. It is a good heat dissipation material that can simultaneously achieve high thermal conductivity and adjustable thermal expansion coefficient.
[0004] However, the existing copper-molybdenum copper-copper composite materials have a thermal conductivity limit due to the thermal conductivity of molybdenum in the core material. In order to break through this limitation, the copper content can generally be increased or the thickness of the surface copper layer and the core molybdenum copper layer can be increased. However, these two methods will lead to an increase in the thermal expansion coefficient of the composite material. Therefore, the composite material still cannot actually have both high thermal conductivity and low expansion coefficient. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to propose a new copper-molybdenum copper-copper composite material with a porous core material and a preparation method thereof. Compared with the existing copper-molybdenum copper-copper composite material, the composite material has higher local thermal conductivity and lower thermal expansion coefficient, which can realize the free assembly or selective assembly of high-heat chips, not only improving the heat dissipation efficiency, but also enhancing the reliability and stability of the system. At the same time, the material effectively reduces the thermal stress caused by temperature changes by accurately controlling the flow direction and speed of heat, prolonging the service life of semiconductor devices, and providing a solid guarantee for the stable operation of high-performance electronic devices in the information age.
[0006] The technical solution of the present invention is as follows: A copper-molybdenum-copper-copper composite material with a porous core material comprises a molybdenum-copper alloy core material and copper material covering the upper and lower surfaces of the core material, wherein the core material is provided with a plurality of holes, namely core material holes, and the core material holes are filled with silicon carbide and / or diamond.
[0007] The inventors unexpectedly discovered that by setting a porous structure in the core material of the copper-molybdenum copper-copper composite material and filling the holes with a filling material that has a higher thermal conductivity than copper and a lower thermal expansion coefficient than molybdenum, and can be perfectly matched with the core material molybdenum copper and the covering material copper through the pore structure without generating obvious thermal stress and structural stress, that is, the silicon carbide and / or diamond selected in the present technical solution, a copper-molybdenum copper-copper heat dissipation material with high thermal conductivity and low expansion coefficient and stable performance and excellent performance can be obtained at the filling material.
[0008] The size, quantity and position of the core material holes can be flexibly adjusted according to the loading requirements of the heating element.
[0009] When the copper-molybdenum-copper-copper composite material with a porous core material of the present invention is used, chips with larger heat dissipation can be loaded at positions filled with silicon carbide and / or diamond, and chips with smaller heat dissipation can be loaded at other positions; and / or a larger number of microchips or their assemblies can be loaded at positions filled with silicon carbide and / or diamond, and a smaller number of chips can be loaded at other positions.
[0010] According to some preferred embodiments of the present invention, the hole is circular or square in shape.
[0011] According to some preferred embodiments of the present invention, the core material holes are arranged symmetrically in one or two rows along the long axis of the core material, with a diameter or length of 1 / 4 to 1 / 2 of the width of the core material, and the number is 1 to 4.
[0012] The present invention further provides a method for preparing a copper-molybdenum-copper-copper composite material having a porous core material, comprising: Opening the core material hole on the molybdenum-copper alloy plate as the core material to obtain the open-hole core material; A first copper plate is covered below the open-hole core material, the core material hole is filled with silicon carbide and / or diamond inserts having the same shape and thickness as the core material hole, and a second copper plate is covered above the open-hole core material after the filling is completed, to obtain a composite material blank; The composite material blank is subjected to discharge plasma processing to obtain the copper-molybdenum-copper-copper composite material with a porous core material.
[0013] In the above preparation method of the present invention, the discharge plasma processing method will not cause significant deformation of the filling material, so that a final product having a structure substantially consistent with the composite material blank can be obtained.
[0014] According to some preferred embodiments of the present invention, obtaining the molybdenum-copper alloy plate includes: Pressing molybdenum powder into billets; The surface of the obtained square billet is covered with a copper plate, and then copper infiltration treatment is performed at 1400-1500° C. in a hydrogen atmosphere to obtain a molybdenum-copper alloy; The molybdenum-copper alloy is subjected to multiple warm rolling, annealing and cold rolling, annealing until it reaches the target thickness, thereby obtaining the molybdenum-copper alloy plate.
[0015] According to some preferred embodiments of the present invention, the thickness ratio of the first copper plate, the core material and the second copper plate is 1~2:4~1:1~2.
[0016] More preferably, the thickness ratio of the first copper plate, the core material and the second copper plate is 1:4:1, 2:3:2, 1:1:1 or 2:1:2.
[0017] According to some preferred embodiments of the present invention, the spark plasma processing includes: loading the composite material blank into a spark plasma sintering furnace for sintering, the sintering heating rate is 95-105°C / min, the sintering temperature is 1100-1300°C, the holding time is 50-70min, and the sintering pressure is 2.3-2.5 kN.
[0018] The present invention has the following beneficial effects: The copper-molybdenum-copper-copper composite material with a porous core material of the present invention has a low thermal expansion coefficient and high thermal conductivity, which not only significantly improves the heat dissipation capacity of the material, but also can carry a variety of chips at different positions according to different needs, thereby optimizing the overall heat dissipation performance and thermodynamic stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the composite structure of the copper-molybdenum-copper-copper composite material with a porous core material of the present invention. DETAILED DESCRIPTION
[0020] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] Example 1 See attached Figure 1 , a copper-molybdenum-copper-copper composite material having a porous core is prepared by the following steps: (1) 329 g of molybdenum powder was placed into a 80 mm × 60 mm mold and pressed into a 80 mm × 60 mm × 10 mm square billet using a molding press; (2) A copper plate with a mass of 184 g was covered on the surface of the square billet, and then placed in a hydrogen atmosphere infiltration furnace for copper infiltration, kept at 1400°C for 2 h, and the excess copper on the alloy surface was milled off to obtain a molybdenum-copper alloy; (3) performing warm rolling, annealing, cold rolling, and annealing on the molybdenum-copper alloy for multiple times until the thickness is 5 mm, thereby obtaining a molybdenum-copper plate; (4) Using wire cutting technology, a circular hole with a diameter of 1 / 2 the width of the molybdenum-copper plate is opened at the center of the molybdenum-copper plate; (5) A 1.85 mm thick copper plate is placed under a 5 mm thick molybdenum-copper composite plate, and the holes on the molybdenum-copper plate are filled with silicon carbide inserts with the same shape as the holes and the same height as the molybdenum-copper plate. Another 1.85 mm thick copper plate is then placed on top of the filled molybdenum-copper plate, and the whole is fixed to obtain a composite material blank; (6) The composite material green body is placed in a spark plasma sintering furnace for sintering to prepare a copper-molybdenum-copper-copper composite material with a porous core material; wherein the sintering heating rate is 100°C / min, the sintering temperature is 1200°C, the sintering pressure is 2.4 kN, and the holding time is 60 min.
[0022] The layer thickness ratio of the copper-molybdenum-copper-copper composite material obtained in this embodiment is 1:4:1, and the core material includes a main material composed of 70wt% molybdenum and 30wt% copper and a filling material composed of silicon carbide.
[0023] Example 2 See attached Figure 1 , a copper-molybdenum-copper-copper composite material having a porous core is prepared by the following steps: (1) 329 g of molybdenum powder was loaded into a 80 mm × 60 mm mold and pressed into a 80 mm × 60 mm × 10 mm square billet using a molding press; (2) A copper plate with a mass of 184 g was covered on the surface of the square billet, and then placed in a hydrogen atmosphere infiltration furnace for copper infiltration, kept at 1400°C for 2 h, and the excess copper on the alloy surface was milled off to obtain a molybdenum-copper alloy; (3) performing multiple warm rolling, annealing, cold rolling, and annealing on the molybdenum-copper alloy until the thickness is 4.5 mm to obtain a molybdenum-copper plate; (4) Using wire cutting technology, two square holes with a length of 1 / 3 of the width of the molybdenum-copper plate are symmetrically opened along the long axis direction at the center of the molybdenum-copper plate; (5) A 3.6 mm thick copper plate is placed under a 4.5 mm thick molybdenum-copper composite plate, and the holes on the molybdenum-copper plate are filled with diamond inserts with the same shape as the holes and the same height as the molybdenum-copper plate. Another 3.6 mm thick copper plate is then placed on top of the filled molybdenum-copper plate, and the whole is fixed to obtain a composite material blank; (6) The composite material green body was placed in a spark plasma sintering furnace for sintering to prepare a copper-molybdenum-copper-copper composite material with a porous core material. The sintering heating rate was 100°C / min, the sintering temperature was 1200°C, the sintering pressure was 2.4 kN, and the holding time was 60 min.
[0024] The layer thickness ratio of the copper-molybdenum-copper-copper composite material obtained in this embodiment is 2: 3: 2, and the core material includes a main material composed of 70wt% molybdenum and 30wt% copper and a filling material composed of diamond.
[0025] Example 3 See attached Figure 1 , a copper-molybdenum-copper-copper composite material having a porous core is prepared by the following steps: (1) 279 g of molybdenum powder was placed into a 80 mm × 60 mm mold and pressed into a 80 mm × 60 mm × 10 mm square billet using a molding press; (2) A copper plate with a mass of 229 g was covered on the surface of the square billet, and then placed in a hydrogen atmosphere infiltration furnace for copper infiltration, kept at 1400°C for 2 h, and the excess copper on the surface of the alloy was milled off to obtain a molybdenum-copper alloy; (3) performing warm rolling, annealing, cold rolling, and annealing on the molybdenum-copper alloy for multiple times until the thickness is 3 mm, thereby obtaining a molybdenum-copper plate; (4) Using wire cutting technology, three circular holes with a diameter of 1 / 4 of the width of the molybdenum-copper plate are opened at the center of the molybdenum-copper plate. The three holes are distributed in an equilateral triangle; (5) A 3.5 mm thick copper plate is placed under a 3 mm thick molybdenum-copper composite plate, and the holes on the molybdenum-copper plate are filled with silicon carbide inserts with the same shape as the holes and the same height as the molybdenum-copper plate. Another 3.5 mm thick copper plate is then covered on top of the filled molybdenum-copper plate, and the whole is fixed to obtain a composite material blank; (6) The composite material green body was placed in a spark plasma sintering furnace for sintering to prepare a copper-molybdenum-copper-copper composite material with a porous core material. The sintering heating rate was 100°C / min, the sintering temperature was 1200°C, the sintering pressure was 2.4 kN, and the holding time was 60 min.
[0026] The layer thickness ratio of the copper-molybdenum-copper-copper composite material obtained in this embodiment is 1: 1: 1, and the core material includes a main material composed of 60wt% molybdenum and 40wt% copper and a filling material composed of silicon carbide.
[0027] Example 4 See attached Figure 1 , a copper-molybdenum-copper-copper composite material having a porous core is prepared by the following steps: (1) 279 g of molybdenum powder was placed into a 80 mm × 60 mm mold and pressed into a 80 mm × 60 mm × 10 mm square billet using a molding press; (2) A copper plate with a mass of 229 g was covered on the surface of the square billet, and then placed in a hydrogen atmosphere infiltration furnace for copper infiltration, kept at 1400°C for 2 h, and the excess copper on the surface of the alloy was milled off to obtain a molybdenum-copper alloy; (3) performing warm rolling, annealing, cold rolling, and annealing on the molybdenum-copper alloy for multiple times until the thickness is 2 mm, thereby obtaining a molybdenum-copper plate; (4) Using wire cutting technology, four square holes with a length of 1 / 4 of the width of the molybdenum-copper plate are symmetrically opened at the center of the molybdenum-copper plate, and the four holes are distributed in a square shape; (5) A 4.5 mm thick copper plate is placed under a 2 mm thick molybdenum-copper composite plate, and the holes on the molybdenum-copper plate are filled with diamond inserts with the same shape as the holes and the same height as the molybdenum-copper plate. Another 4.5 mm thick copper plate is then placed on top of the filled molybdenum-copper plate, and the whole is fixed to obtain a composite material blank; (6) The composite material green body was placed in a spark plasma sintering furnace for sintering to prepare a copper-molybdenum-copper-copper composite material with a porous core material. The sintering heating rate was 100°C / min, the sintering temperature was 1200°C, the sintering pressure was 2.4 kN, and the holding time was 60 min.
[0028] The layer thickness ratio of the copper-molybdenum-copper-copper composite material obtained in this embodiment is 2: 1: 2, and the core material includes a main material composed of 60wt% molybdenum and 40wt% copper and a filling material composed of diamond.
[0029] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A copper-molybdenum-copper-copper composite material with a porous core material, comprising a core material of a molybdenum-copper alloy and a copper material covering the upper surface and the lower surface of the core material, characterized in that: The core material is provided with a plurality of holes, namely core material holes, and the core material holes are filled with silicon carbide and / or diamond.
2. The copper-molybdenum-copper-copper composite material with a porous core material according to claim 1, characterized in that: The shape of the core material hole is circular or square.
3. The copper-molybdenum-copper-copper composite material with a porous core material according to claim 1, characterized in that: The core material holes are arranged symmetrically in one or two rows along the long axis of the core material, with a diameter or length of 1 / 4 to 1 / 2 of the width of the core material, and the number of the holes is 1 to 4.
4. The method for preparing the copper-molybdenum-copper-copper composite material having a porous core material according to any one of claims 1 to 3, characterized in that: It includes: Opening the core material hole on the molybdenum-copper alloy plate as the core material to obtain the open-hole core material; A first copper plate is covered below the open-hole core material, the core material hole is filled with silicon carbide and / or diamond inserts having the same shape and thickness as the core material hole, and a second copper plate is covered above the open-hole core material after the filling is completed, to obtain a composite material blank; The composite material blank is subjected to discharge plasma processing to obtain the copper-molybdenum-copper-copper composite material with a porous core material.
5. The preparation method according to claim 4, characterized in that: The molybdenum-copper alloy plate is obtained by: Pressing molybdenum powder into billets; The surface of the obtained square billet is covered with a copper plate, and then copper infiltration treatment is performed at 1400-1500° C. in a hydrogen atmosphere to obtain a molybdenum-copper alloy; The molybdenum-copper alloy is subjected to multiple warm rolling, annealing and cold rolling, annealing until it reaches the target thickness, thereby obtaining the molybdenum-copper alloy plate.
6. The preparation method according to claim 4, characterized in that: The thickness ratio of the first copper plate, the core material and the second copper plate is 1-2:4-1:1-2.
7. The preparation method according to claim 6, characterized in that: The thickness ratio of the first copper plate, the core material and the second copper plate is 1:4:1, 2:3:2, 1:1:1 or 2:1:
2.
8. The preparation method according to claim 4, characterized in that: The spark plasma processing comprises: placing the composite material blank into a spark plasma sintering furnace for sintering, the sintering heating rate is 95-105°C / min, the sintering temperature is 1100-1300°C, the holding time is 50-70min, and the sintering pressure is 2.3-2.5 kN.